Ophiocordyceps salganeicola, a parasite of social cockroaches in Japan and insights into the evolution of other closely-related Blattodea-associated lineages - João P. M. Araújo; Mitsuru G. Moriguchi; Shigeru Uchiyama; Noriko Kinjo; Yu Matsuura (IMA Fungus)
Abstract The entomopathogenic genus Ophiocordyceps includes a highly diverse group of fungal species, predominantly parasitizing insects in the orders Coleoptera, Hemiptera, Hymenoptera and Lepidoptera. However, other insect orders are also parasitized by these fungi, for example the Blattodea (termites and cockroaches). Despite their ubiquity in nearly all environments insects occur, blattodeans are rarely found infected by filamentous fungi and thus, their ecology and evolutionary history remain obscure. In this study, we propose a new species of Ophiocordyceps infecting the social cockroaches Salganea esakii and S. taiwanensis, based on 16 years of collections and field observations in Japan, especially in the Ryukyu Archipelago. We found a high degree of genetic similarity between specimens from different islands, infecting these two Salganea species and that this relationship is ancient, likely not originating from a recent host jump. Furthermore, we found that Ophiocordyceps lineages infecting cockroaches evolved around the same time, at least twice, one from beetles and the other from termites. We have also investigated the evolutionary relationships between Ophiocordyceps and termites and present the phylogenetic placement of O. cf. blattae. Our analyses also show that O. sinensis could have originated from an ancestor infecting termite, instead of beetle larvae as previously proposed.